Fiscal uncertainty and sovereign credit risk - Hantzsche, Arno (2018)
This doctoral thesis studies sovereign credit risk during periods of uncertainty about the state of a government's fiscal position. A new measure of fiscal uncertainty is introduced, based on the disagreement in official forecasts of the public budget deficit, and forecast revisions to approximate common uncertainty shocks. It is shown that in the aftermath of the global financial crisis, fiscal uncertainty increased substantially in advanced economies. The effects of fiscal uncertainty are largely unknown, in particular in the context of sovereign credit risk. To estimate the response of sovereign credit ratings to fiscal uncertainty, a new empirical framework is developed for the analysis of rating determinants. Rating transition is modelled as the joint outcome of two processes, which determine the frequency of rating changes, and their direction. This thesis finds that fiscal uncertainty is perceived a credit risk by rating agencies and increases the probability of a rating downgrade. Fiscal uncertainty also affects the attention paid to sovereign ratings. An event study analysis shows that the attention to rating announcements increases, the more noisy publicly available information about fiscal outcomes is.